PEMBUATAN GAME THE CROSSING - Ryan Djoenaidi; Jeanny Pragantha; Darius Andana H (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Over the past decade, game industries have developed games with long storyline, complex gameplay, and high quality realistic graphics. These games are mostly offline games which tend to disrupt the players social activities and also significantly occupy their time.The Crossing is a math-themed action flash game which requires both fast fingers and quick calculation in order to earn high score. As a web game, The Crossing allows the player to join the competition with other players to achieve the highest score in game and therefore creates a community. With simple gameplay and short game time, The Crossing is intended not to occupy significant amount of players time. Key wordsAction Script 3, Adobe Flash CS6, flash game, social game, The Crossing